RNA sequencing reveals distinct gene expression patterns during the development of parasitic larval stages of the salmon louse (Lepeophtheirus salmonis). Issue 6 (25th January 2018) - Eichner, C; Dondrup, M; Nilsen, F
Abstract: The salmon louse ( Lepeophtheirus salmonis ), an ectoparasitic copepod on salmonids, has become a major threat for the aquaculture industry. In search for new drugs and vaccines, transcriptome analysis is increasingly used to find differently regulated genes and pathways in response to treatment. However, the underlying gene expression changes going along with developmental processes could confound such analyses. The life cycle of L. salmonis consists of eight stages divided by moults. The developmental rate of salmon lice on the host is not uniform. Individual‐ and sex‐related differences are found leading to individuals of unlike developmental status at same sampling time point after infection. In this study, we analyse L. salmonis from a time series by RNA sequencing applying a method of separating individuals of different instar age independent of sampling time point. Lice of four stages divided into up to four age groups within the stage were analysed in triplicate (total of 66 samples). Gene expression analysis shows that the method for sorting individuals was successful. Many genes show cyclic expression patterns over the moulting cycles. Overall gene expression differs more between lice of different age within the same stage than between lice of different stage but same instar age.